(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
One of the major changes in contemporary ecology is the recognition of the flow of individuals between communities as a main determinant of their local structure. This flow of individuals depends on the spatial structure of the landscape and the dispersal capacity of the species involved. Notably, when landscape structure is considered, it has turned out to be of equal or greater importance compared to the classic local determinants such as area, heterogeneity or productivity. Herein, we focus on the role of landscape configuration and the dispersal capacity of organisms on biodiversity patterns, with special emphasis on the research developed by the authors.